2013
DOI: 10.2174/2210315511303030001
|View full text |Cite
|
Sign up to set email alerts
|

The Comparison of Rat and Human Intestinal and Hepatic Glucuronidation of Enterolactone Derived from Flaxseed Lignans

Abstract: The mammalian lignan, enterolactone (EL), is a gut microbe metabolite of plant lignan secoisolariciresinol diglucoside (SDG), which is most abundant in flaxseed. Numerous epidemiological, experimental and clinical studies suggest the protective effects of EL against various chronic diseases such as cancer, cardiovascular disease, and inflammation. However, EL's oral bioavailability is low and highly variable due to extensive first-pass metabolism, especially glucuronidation, which results in the large amount o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 159 publications
0
10
0
Order By: Relevance
“…The ability of the gastrointestinal mucosa to contribute significantly to pre-systemic metabolism is also supported by the finding that ED and EL are largely found as glucuronic acid and sulphate conjugates in the portal vein of rats following an oral administration of flaxseed lignans ( 32 ) . A relatively higher contribution of intestinal glucuronidation compared with liver glucuronidation has been suggested for EL in an in vitro liver microsomal enzyme kinetic study ( 23 ) . Other studies have also suggested the contribution of both phase II enzyme conjugates and, to a minor extent, aromatic hydroxylated metabolites of ED and EL in rat, pig, rhesus monkey and human liver microsomes ( 21 , 33 36 ) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability of the gastrointestinal mucosa to contribute significantly to pre-systemic metabolism is also supported by the finding that ED and EL are largely found as glucuronic acid and sulphate conjugates in the portal vein of rats following an oral administration of flaxseed lignans ( 32 ) . A relatively higher contribution of intestinal glucuronidation compared with liver glucuronidation has been suggested for EL in an in vitro liver microsomal enzyme kinetic study ( 23 ) . Other studies have also suggested the contribution of both phase II enzyme conjugates and, to a minor extent, aromatic hydroxylated metabolites of ED and EL in rat, pig, rhesus monkey and human liver microsomes ( 21 , 33 36 ) .…”
Section: Discussionmentioning
confidence: 99%
“…These lignans undergo significant first-pass metabolism (mainly conjugative with glucuronic acid and sulphate, along with a small amount of cytochrome P450 enzyme-mediated metabolism to form principally monohydroxylated products) and enterohepatic recirculation ( 21 , 22 ) . Lin et al ( 23 ) demonstrated that both intestinal and liver microsomes contributed significantly to the glucuronidation of EL. Flaxseed lignans are excreted mainly as enterolignan conjugates, glucuronides and sulphates, via urine, faeces and bile along with small amounts of lignan aglycones ( 24 , 25 ) .…”
mentioning
confidence: 99%
“…After conversion of lignans into ED and EL, these enterolignans are absorbed in the large intestine followed by conjugation as glucuronides and sulfates based on in vitro work using human colon epithelial cells [34]. Conjugated EL and ED undergo extensive first-pass metabolism and enterohepatic recirculation [34,35], as well as deconjugation by colonic bacterial β-glucuronidases and sulfatases followed by reabsorption [36]. It has also been shown that conjugation of EL takes place not only in the colon, but also in the small intestine and liver microsomes of humans and rats according to in vitro enzymatic kinetic analysis of EL glucuronidation [35].…”
Section: Metabolism Of Lignans In the Gastrointestinal Tractmentioning
confidence: 99%
“…This likely influenced the plasma concentration of EL at 48 h (d 7 of life) because the concentration of EL in MR averaged 123 nmol/L. It has been shown in vitro using human colon epithelial cells (Jansen et al, 2005) or rat and human intestinal and liver microsomes (Lin et al, 2013) that EL and ED are conjugated as glucuronides and sulfates. Conjugated EL and ED undergo extensive first-pass metabolism and enterohepatic recirculation (Jansen et al, 2005;Lin et al, 2013), as well as deconjugation by bacterial β-glucuronidases and sulfatases followed by reabsorption (Setchell and Adlercreutz 1988).…”
mentioning
confidence: 99%
“…It has been shown in vitro using human colon epithelial cells (Jansen et al, 2005) or rat and human intestinal and liver microsomes (Lin et al, 2013) that EL and ED are conjugated as glucuronides and sulfates. Conjugated EL and ED undergo extensive first-pass metabolism and enterohepatic recirculation (Jansen et al, 2005;Lin et al, 2013), as well as deconjugation by bacterial β-glucuronidases and sulfatases followed by reabsorption (Setchell and Adlercreutz 1988). In lactating dairy cows, absorption of EL and ED appears to occur in the rumen (Gagnon et al, 2009) and intestines (Njåstad et al, 2014), likely as conjugated forms.…”
mentioning
confidence: 99%